Hubungan pola makan, tingkat stres, dan konsumsi kopi dengan kejadian gastritis pada pasien di poli penyakit dalam - Tatu, Muslima S.; Kadir, Sunarto; Abudi, Ramly (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Gastritis is a health disorder related to the digestive process, especially the stomach. Frequently emptying the stomach can cause damage, as the stomach wall is compressed, causing abrasions and ulcers. These ulcers can lead to inflammation. Purpose: To determine the relationship between diet, stress levels, and coffee consumption and the incidence of gastritis in patients attending the internal medicine clinic. Method: This study was quantitative, with a cross-sectional approach. The population was 60 patients and the sample size was 52 patients, using a purposive sampling technique. Data were analyzed using the chi-square test. Results: Univariate testing revealed that the most common dietary pattern was poor (23 respondents (44.2%), the most common stress level was severe (16 respondents (30.8%), and the most common coffee consumption was poor (36 respondents (69.2%). Bivariate results showed an association between dietary patterns and the incidence of gastritis (p-value = 0.024 <0.005), stress levels with the incidence of gastritis (p-value = 0.001 <0.005), and coffee consumption with the incidence of gastritis (p-value = 0.000 <0.005). Conclusion: There is a relationship between dietary patterns, stress levels, and coffee consumption with the incidence of gastritis in patients in the internal medicine clinic. Keywords: Coffee Consumption; Diet; Gastritis Incidence; Stress Level. Pendahuluan: Gastritis merupakan gangguan kesehatan terkait proses pencernaan terutama lambung. Lambung bisa mengalami kerusakan jika sering kosong, karena lambung akan meremas hingga dinding lambung lecet dan luka, dengan adanya luka tersebut lambung akan mengalami proses inflamasi. Tujuan: Untuk mengetahui hubungan pola makan, tingkat stres, dan konsumsi kopi dengan kejadian Gastritis pada pasien di poli penyakit dalam. Metode: Jenis penelitian adalah kuantitatif, pendekatan cross-sectional, populasi penelitian berjumlah 60 pasien, sampel penelitian berjumlah 52 pasien, menggunakan teknik purposive sampling. Analisis data uji chi-square. Hasil: Pengujian univariat menunjukkan pola makan pasien terbanyak pola makan kurang 23 responden (44.2%), tingkat stres pasien terbanyak stres berat 16 responden (30.8%), konsumsi kopi terbanyak konsumsi kopi buruk 36 responden (69,2%). Hasil bivariat menunjukkan pola makan dengan kejadian Gastritis (p-value = 0,024<0,005), tingkat stres dengan kejadian Gastritis (p-value = 0,001<0,005), konsumsi kopi dengan kejadian Gastritis (p-value = 0,000<0,005). Simpulan: Ada hubungan pola makan, tingkat stres dan konsumsi kopi dengan kejadian Gastritis pada pasien di poli penyakit dalam. Kata Kunci: Kejadian Gastritis; Konsumsi Kopi; Pola Makan; Tingkat Stres.